2019
DOI: 10.1177/1010428319845749
|View full text |Cite
|
Sign up to set email alerts
|

Common matrix metalloproteinase-2 gene variants and altered susceptibility to breast cancer and associated features in Tunisian women

Abstract: A role for matrix metalloproteinase polymorphisms in breast cancer development and progression was proposed, but with inconclusive results. We assessed the relation of matrix metalloproteinase-2 variants with breast cancer and related phenotypes in Tunisians. This case-control retrospective study involved 430 women with breast cancer and 498 healthy controls. Genotyping of matrix metalloproteinase-2 rs243866, rs243865, rs243864, and rs2285053 was analyzed by allelic exclusion. The minor allele frequency of rs2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
3
16
2
Order By: Relevance
“…Leptin and LEPR Q223R (rs1137101) were identified as risk factors for breast cancer in Egyptian and Nigerian women ( 139 141 ) while leptin alone was notably reported as a key driver of breast cancer progression through the induction of JAK/STAT3 , ERK1/2 , and estrogen pathways in obese Egyptian women ( 142 ). Furthermore, variants of VEGF and MMPs , which induce the upregulation of these proteins, were reported as risk factors in North African countries of Morocco, Egypt, and Tunisia ( 143 148 ). Other overexpressed angiogenic proteins reported are EGFR in Tunisia ( 149 ) and IGFBP2 and IGFBP5 in Nigerian women ( 150 ).…”
Section: Resultsmentioning
confidence: 99%
“…Leptin and LEPR Q223R (rs1137101) were identified as risk factors for breast cancer in Egyptian and Nigerian women ( 139 141 ) while leptin alone was notably reported as a key driver of breast cancer progression through the induction of JAK/STAT3 , ERK1/2 , and estrogen pathways in obese Egyptian women ( 142 ). Furthermore, variants of VEGF and MMPs , which induce the upregulation of these proteins, were reported as risk factors in North African countries of Morocco, Egypt, and Tunisia ( 143 148 ). Other overexpressed angiogenic proteins reported are EGFR in Tunisia ( 149 ) and IGFBP2 and IGFBP5 in Nigerian women ( 150 ).…”
Section: Resultsmentioning
confidence: 99%
“…Such covariates were selected, as these covariates were chosen as the primary control covariates. 14 As calculated by the BMI, core obesity tends to have a greater effect on the prevalence of breast cancer in African-American females than general adiposity. The pre-menopausal women have 21% an elevated value of BMI and 29% of post-menopausal women with an abdomen diameter of 90 cm are also more likely to develop breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Altered MMP-2 activity arising from the involvement of unique MMP-2, this included variants in the degrade of ECM and disturbance of the membrane barrier in the basement. 14 MMP-2 protein has been regulated by immune histochemical approaches in breast carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the T allele reduces the expression of MMP-2 (35). Ten studies investigated the association between rs243865 and breast cancer risk, but the results were unclear (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Several authors have hypothesized that this polymorphism may reduce the risk of breast cancer because of less protein expression.…”
Section: Mmp-2 Gene Polymorphisms and Breast Cancer Riskmentioning
confidence: 99%
“…Three studies were identified that investigated the association between rs2285053 in MMP-2 and breast cancer risk. Two studies showed that the rs2285053 T allele rather than the C allele reduced the risk of breast cancer in the Tunisian (OR=0.59; 95% CI=0.46-0.75) (23) and Iranian (OR=0.61; 95% CI=0.37-0.99; p=0.049) (38) populations. However, Beeghly-Fadiel et al (18) did not find any association between CC, CT, TT genotypes of rs2285053 and breast cancer risk in additive models (p=0.436).…”
Section: Mmp-2 Gene Polymorphisms and Breast Cancer Riskmentioning
confidence: 99%